PENGARUH WORK-LIFE BALANCE, BURNOUT, DAN COMPETENCE TERHADAP KEPUASAN KERJA TENAGA KESEHATAN - Malini, Helma; Yulianty, Yulianty (Bagian Penelitian & Pengabdian Masyarakat STIKES Adi Husada, 2023)
Background & Aims: This study seeks to investigate and analyze the relationship between Work-Life Balance, Burnout, and Competence and Nurse Job Satisfaction at Rumah Sakit Umum Soedarso. The reason this research conducted were because many health worker were burnout and resigning from their works. Regional Public Hospital Method: questionnaire designed by the author, 338 health workers were surveyed to collect data. Using a probability-based sampling technique, 80 nurses were selected as samples, and the data were analyzed using Multiple Linear Regression Analysis Results: Work-Life Balance is positively correlated with job satisfaction (P 0.05), whereas Burnout is negatively correlated with job satisfaction (P 0.05), and Competence is positively correlated with job satisfaction (P 0.01). Work Life Balance has a positive and significant effect on Nurse Job Satisfaction at Rumah Sakit Umum Soedarso Pontianak; Burnout has a negative and significant effect; and Competence has a positive and significant effect on Nurse Job Satisfaction at Rumah Sakit Umum Soedarso Pontianak Conclusion: The conclusion that can be drawn is that hospitals must pay attention to early indications of fatigue so that they can prevent the resignation of health workers and in order to increase productivity by providing facilities that can improve work balance.